The influence of external reference price strategies in a nonprofit arts organization's “pay-what-you-want” setting - Hellen P. Gross; Maren Rottler; Franziska Wallmeier (Journal of Philanthropy and Marketing (NVSM), 2021)
Nonprofit arts organizations face conflicting objectives to balance—or more specifically, to create—artistic and educational value and to generate financial income from various sources. Pay-what-you-want (PWYW), a participative pricing mechanism where services have no fixed price and customers actively decide what to pay, is a novel pricing mechanism and is of high interest for organizations and researchers alike. Based on the concepts of loss aversion and gain, this study presents a field experiment to test the effects of different PWYW pricing strategies on the amount of money paid by visitors of a German photo biennial. Explicitly, the provisions of minimum, maximum, and suggested external reference prices are compared to a setting with no external reference prices. We test the derived hypotheses, discuss the results, and provide implications for future research, as well as for the management of nonprofit arts organizations.
Keywords: 650; external reference price; internal reference price; nonprofit arts organizations; pay-what-you-want; pricing strategy